Metabolic faecal fingerprinting of trans-resveratrol and quercetin following a high-fat sucrose dietary model using liquid chromatography coupled to high-resolution mass spectrometry1. Issue 8 (5th August 2015) - Etxeberria, Usune; Arias, Noemi; Boqué, Noemí; Romo-Hualde, Ana; Macarulla, M. Teresa; Portillo, María P.; Milagro, Fermín I.; Martínez, J. Alfredo
<x xml:space="preserve">Abstract</x> Untargeted metabolomics distinguishes individuals into clusters based on the physiological impact of the dietary treatment to which they have been subjected.